2021
DOI: 10.3390/ijerph18189812
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Arsenic Oxyanions from Water by Ferric Chloride—Optimization of Process Conditions and Implications for Improving Coagulation Performance

Abstract: The chronic ingestion of arsenic (As) contaminated water has raised significant health concerns worldwide. Iron-based coagulants have been widely used to remove As oxyanions from drinking water sources. In addition, the system’s ability to lower As within the maximum acceptable contamination level (MCL) is critical for protecting human health from its detrimental effects. Accordingly, the current study comprehensively investigates the performance of As removal under various influencing factors including pH, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
7
1
1
Order By: Relevance
“…As can be seen from Figure 7a, the zeta potential of the iron (III) hydroxide precipitate particles formed in our experiments in the absence of nickel ions in the model solution is positive at pH < 5.4 and becomes negative at pH > 5.4 (Figure 7a, curve 1). The point of zero charge corresponds to pH = 5.4, which significantly differs from the data of works (Inam et al, 2021;Liu et al, 2021;Villalobos & Antelo, 2011), where the pH of the point of zero charge for ferrihydrite was 8.8, 8.4 and 7.5, respectively. We ascribe the observed difference to the presence of sulfate ions in the model solution in our experiments, as well as to a small possible admixture of iron (III) hydroxycarbonate FeOHCO 3 in the formed precipitates.…”
Section: Physicochemical Properties Of the Formed Iron (Iii) Hydroxid...contrasting
confidence: 86%
“…As can be seen from Figure 7a, the zeta potential of the iron (III) hydroxide precipitate particles formed in our experiments in the absence of nickel ions in the model solution is positive at pH < 5.4 and becomes negative at pH > 5.4 (Figure 7a, curve 1). The point of zero charge corresponds to pH = 5.4, which significantly differs from the data of works (Inam et al, 2021;Liu et al, 2021;Villalobos & Antelo, 2011), where the pH of the point of zero charge for ferrihydrite was 8.8, 8.4 and 7.5, respectively. We ascribe the observed difference to the presence of sulfate ions in the model solution in our experiments, as well as to a small possible admixture of iron (III) hydroxycarbonate FeOHCO 3 in the formed precipitates.…”
Section: Physicochemical Properties Of the Formed Iron (Iii) Hydroxid...contrasting
confidence: 86%
“…Although the comparison was made repeatedly using different types and shapes of mixers, findings still indicate that the performance of ferric chloride is not impacted by temperature. In contrast, other investigations have shown that ferric chloride as a coagulant was influenced by temperature (Duan & Gregory, 2003;Inam et al, 2021).…”
Section: Ferric Chloride As a Coagulantmentioning
confidence: 84%
“…Temperature and type of coagulant are equally effective on the coagulation efficiency (Duan & Gregory, 2003;Rodrigues et al, 2008). Temperature can affect the metal ion hydrolysis reaction rate (Inam et al, 2021). A higher temperature causes an enhanced reaction rate and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…The residual As(III, V) and Fe(III) concentrations were analyzed after filtering the supernatant using a 0.45µm glass filter. For all chemical coagulation experiments, the sequential experimental strategy was as follows: 3 min fast agitation (coagulation); 20 min slow mixing; 30 min quiescent settling; and aliquot collection [20]. However, only slow mixing for 25 min was done for kinetic experiments, with the rest of the experimental protocol remaining same.…”
Section: Experimental Designmentioning
confidence: 99%
“…However, how the sorption properties of FHO for As(III, V) species vary with temperature needs significant attention. Several studies have also focused on the sorption potential and removal mechanism of As oxyanions onto and from FHO by coagulation [10,20]. Still, the literature comparing the sorption capacity and rate of FHO for trivalent and pentavalent As oxyanions in complex waters seems scarce.…”
Section: Introductionmentioning
confidence: 99%